Mathematics I - Kostra, Juraj (Univerzita Pardubice, 2019)
This textbook is intended for students of the Örst-year Mathematics at the Faculty of Chemical Technology, University of Pardubice. It introduces the reader to the basics of linear algebra and di§erential and integral calculus of one variable as demanded for undergraduate study of chemistry and related Öelds. It is also appedned with an introduction to complex numbers.
Keywords: Přírodní vědy